A Foreigner who Does Not Steal My Job: The Role of Unemployment Risk and Values in Attitudes toward Equal Opportunities1. Issue 3 (September 2016) - Pecoraro, Marco; Ruedin, Didier
Immigration has become systematically politicized and opposed by many individuals. We examine individual attitudes toward equal opportunities for foreigners and Swiss citizens, using cross-sectional data from the Swiss Household Panel. Individuals with low levels of education tend to oppose foreigners, while the opposition by individuals with high levels of education increases with the risk of unemployment. Values and beliefs explain the negative attitudes of individuals with low levels of education, but not the association with the risk of unemployment for individuals with high levels of education. Clearly, both values and economic factors are important for explaining attitudes toward foreigners.